Discharge Plan: A Care Tool - Chronic Disease Dyad - Campos de Aldana, Maria Stella; Durán Niño , Erika Yurley; Ruiz-Roa , Silvia Liliana; Páez Esteban , Astrid Nathalia (Revista Cuidarte, 2023)
Introduction: The WHO reports an increase in chronic non-communicable diseases. Given the complexity of these diseases, patients are constantly hospitalized; therefore, it is necessary to strengthen the competence of both patients and caregivers at home to take care of the disease using the program “discharge plan.” Objective: To determine the change in care competency following the implementation of the tool “discharge plan” in a second-level care facility for in-home care of the chronically ill person and family caregiver dyad. Materials and Methods: Quantitative, quasi-experimental study, with pre-test and post-test design, using the “Characterization of the patient-caregiver dyad” form and the “CUIDAR” instrument. The population consisted of 62 dyads. Non-probabilistic convenience sampling was used. Pre- and post-delta was calculated, and paired Student t-test was used for comparison. Results: The “discharge plan” program increased the patients’ dimensions of Knowledge by a delta of 3.2, Uniqueness by 3.0, and total care competency by 10.3. Family caregivers’ competencies improved in the dimensions of Knowledge by a delta of 3.34, Uniqueness by 1.5, Enjoyment by 1.7, and Reciprocity-relationship by 1.61, for a total competency score of 9.2. Discussion and conclusions: These findings suggest that the discharge plan program must be strengthened during hospitalization and discharge to improve the homecare competency of chronically ill patients and their family caregivers.How to cite this article: Campos de Aldana MS, Durán- Niño EY, Ruiz-Roa Silvia Liliana, Páez Esteban AN. Plan de egreso: herramienta del cuidado-diada con enfermedad crónica.  Revista Cuidarte. 2023;14(1):e2754. http://dx.doi.org/10.15649/cuidarte.2754
Keywords: Patient Discharge; Care; Chronic Disease